PHYSICAL QUALITY OF ELEPHANT GRASS (Pennisetum purpureum) SILAGE WITH THE ADDITION OF CALIANDRA LEAF MEAL - L., Oktavia; Cakra, I G. L. O.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika, 2024)
The study aimed to determine the effect of adding calliandra leaf meal on the physical quality of elephant grass ( Pennisetum purpureum ) silage. The research was conducted at the This research was conducted at Sesetan Research Station and Nutrition and Animal Feed Laboratory, Faculty of Animal Husbandry, Udayana University.This study conducted for 2 months, using a completely randomized design consisted of 4 treatments and 5 replications. The treatment were K1 = 95% elephant grass + 0% calliandra leaf meal + 5% molases, K2 = 85% elephant grass + 10% calliandra leaf meal + 5% molases, K3 = 75% elephant grass + 20% calliandra leaf meal + 5% molases, K4 = 65% elephant grass + 30% calliandra leaf meal + 5% molases. There were 4 variables observed, namely color, aroma, texture, presence of fungi, and the pH of the silage. The pH data were analyzed by means of variance and the physical quality values were analyzed by using the frequency distribution. The results of this study found that K1 got the best physical quality value compared to other treatments on the color, texture and pH variables. The addition of calliandra leaf meal increased the pH value of the silage. The conclusion of this study was the elephant grass ( Pennisetum purpureum ) silage with the addition of calliandra leaf flour has not been able to improve the physical quality of silage seen from the variables of color, smell, texture, and pH. Elephant grass silage without the addition of calliandra leaf meal produces the best physical quality.